Health promoting behaviors in adolescence: validation of the Portuguese version of the Adolescent Lifestyle Profile - Pedro Sousa; Pedro Gaspar; Helena Fonseca; Constance Hendricks; Carolyn Murdaugh (Jornal de Pediatria, 2015)
Objective: Reliable and valid instruments are essential for understanding health-promoting behaviors in adolescents. This study analyzed the psychometric properties of the Portuguese version of the Adolescent Lifestyle Profile (ALP). Methods: A linguistic and cultural translation of the ALP was conducted with 236 adolescents from two different settings: a community (n = 141) and a clinical setting (n = 95). Internal consistency reliability and confirmatory factor analysis were performed. Results: Results showed an adequate fit to data, yielding a 36-item, seven-factor structure (CMIN/DF = 1.667, CFI = 0.807, GFI = 0.822, RMR = 0.051, RMSEA = 0.053, PNFI = 0.575, PCFI = 0.731). The ALP presented a high internal consistency (α = 0.866), with the subscales presenting moderate reliability values (from 0.492 to 0.747). The highest values were in Interpersonal Relations (3.059 ± 0.523) and Positive Life Perspective (2.985 ± 0.588). Some gender differences were found. Findings showed that adolescents from the clinic reported an overall healthier lifestyle than those from the community setting (2.598 ± 0.379 vs. 2.504 ± 0.346; t = 1.976, p = 0.049). Conclusion: The ALP Portuguese version is a psychometrically reliable, valid, and useful measurement instrument for assessing health-promoting lifestyles in adolescence. The ALP is cross-culturally validated and can decisively contribute to a better understanding of adolescent health promotion needs. Additional research is needed to evaluate the instrument's predictive validity, as well as its clinical relevance for practice and research. Resumo: Objetivo: Os instrumentos confiáveis e válidos são fundamentais para entender os estilos de vida de promoção da saúde de adolescentes. Este estudo analisa as propriedades psicométricas da versão em português do Perfil do Estilo de Vida Adolescente (ALP). Métodos: Foi realizada uma tradução linguística e cultural do ALP com 236 adolescentes de duas configurações diferentes: uma configuração de comunidade (N = 141) e uma clínica (N = 95). Foram realizadas uma análise da confiabilidade da coerência interna e uma análise fatorial confirmatória. Resultados: Os resultados mostraram-se adequados aos dados, gerando uma estrutura de 7 fatores com 36 itens (CMIN/DF = 1,667, IAC = 0,807, GFI = 0,822, RMR = 0,051, RMSEA = 0,053, PNFI = 0,575, PCFI = 0,731). O ALP apresentou grande coerência interna (α = 0,866), com as subescalas apresentando valores de confiabilidade moderados (de 0,492 a 0,747). Os maiores valores foram de Relações Interpessoais (3,059 ± 0,523) e Perspectiva de Vida Positiva (2,985 ± 0,588). Foram encontradas algumas diferenças entre os sexos. Os achados mostraram que os adolescentes da clínica relataram um estilo de vida mais saudável em geral que os da configuração da comunidade (2,598 ± 0,379 em comparação a 2,504 ± 0,346; t = 1,976, p = 0,049). Conclusão: A versão em português do ALP é um instrumento de mensuração psicometricamente confiável, válido e útil para avaliar os estilos de vida de promoção da saúde na adolescência. O ALP é validado em diferentes culturas e pode contribuir de forma decisiva para um melhor entendimento das necessidades de promoção da saúde na adolescência. É necessária uma pesquisa adicional para avaliar a validade preditiva do instrumento, bem como sua relevância clínica para a prática e pesquisa. Keywords: Lifestyle, Adolescents, Instrument validation, Portuguese, Health-promoting, Psychometric, Palavras-chave: Estilo de vida, Adolescentes, Validação instrumental, Português, Promoção da saúde, Psicometria